PENGARUH JUS KACANG PANJANG PADA IBU HAMIL ANEMIA TRIMESTER 1 TERHADAP PENINGKATAN KADAR HEMOGLOBIN - Tuti Meihartati (Jurnal Medika : Karya Ilmiah Kesehatan, 2019)
Anemia is caused by iron deficiency in the body, a body that lacks iron becomes dizzy, the body feels weak. From interviewing 10 first trimester pregnant women, 7 pregnant women said dizziness, weakness, conjunctiva anemis. Long bean juice is a therapy to increase hemoglobin levels. This study aims to determine the effect of long bean juice on increasing hemoglobin levels in pregnant women in the first trimester The study design was Quasi Experimental with Pre And Post Test Without Control. The study sample were 16 first trimester pregnant women with Purposive Sampling technique. The results of the study by using the Wilcoxon test obtained p value <0.005 (0.001) it means that there was an effect of long bean juice on first trimester anemia pregnant women with an increase in hemoglobin levels The conclusion of this study, there was effect of long bean juice on first trimester anemia pregnant women with an increase in hemoglobin levels. It was recommended that long bean juice be used as a SOP in midwifery care for pregnant women to increase hemoglobin levels.